Behavioral Inhibition/Activation Systems and Depression Among Females With Substance Use Disorder: The Mediating Role of Intolerance of Uncertainty and Anhedonia - Xie, Jinlan; Fang, Ping; Zhang, Zhihao; Luo, Ronglei; Dai, Bibing (Frontiers in Psychiatry, 2021)
Previous studies have shown that the behavioral inhibition/activation systems (BIS/BAS) have substantial effects on substance use disorder and emotional disorders, and substance use disorder and emotional disorders often cooccur; in particular, females with substance use disorder are more likely to also have serious emotional disorders including depression than their male counterparts. However, the associations between the BIS/BAS and depression in females with substance use disorder have received little attention. Furthermore, the underlying mechanisms of these relations are largely unknown. The present study examines the mediating roles of intolerance of uncertainty and anhedonia in the associations between the BIS/BAS and depression among females with substance use disorder from the Research Domain Criteria (RDoC) framework. A total of 303 females with substance use disorder from a compulsory substance abuse detention center were tested using a cross-sectional survey involving BIS/BAS Scales, Intolerance of Uncertainty Scale, Snaith-Hamilton Pleasure Scale, and Center for Epidemiologic Studies Depression Scale. The path analysis model revealed that both the BIS and BAS had a direct effect on depression, that the BIS had an indirect effect on depression through intolerance of uncertainty, and that the BAS had an indirect effect on depression via anhedonia. These findings contribute to a more thorough understanding of how the BIS/BAS influence depression among females with substance use disorder and suggest that the utility of targeting these associations in treatments would help reduce depression in females with substance use disorder.